2018
DOI: 10.4103/jips.jips_121_18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotics on the amount and pH of saliva in edentulous patients: A Prospective study

Abstract: This study concluded that probiotics increase the amount of saliva of completely edentulous patients and so it can be helpful in patients suffering from xerostomia/hyposalivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…As it was mentioned above, BF also contains probiotics. There is some evidence that topical probiotics may increase salivary flow rate [97,98]. Also, probiotics have been reported to decrease plaque formation [99][100][101][102][103][104].…”
Section: Discussionmentioning
confidence: 99%
“…As it was mentioned above, BF also contains probiotics. There is some evidence that topical probiotics may increase salivary flow rate [97,98]. Also, probiotics have been reported to decrease plaque formation [99][100][101][102][103][104].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a high-frequency consumption of probiotic supplements was associated with xerostomia. In contrast, another cross-sectional study suggested that probiotics may lower the risk of xerostomia as their use increases salivation [21]. Gut dysbiosis was linked to several autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus, Behcet's disease, and Sjogren's syndrome [22].…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics increase saliva production in edentulous patients, which helps xerostomia/hyposalivation. Patients receiving regular probiotics have significantly increased saliva volume and moderately changing saliva pH [ 51 ]. Probiotic strains change saliva’s immunoglobulins and mucins, according to animal research.…”
Section: Probiotics Palliate Ailments In the Oral Cavitymentioning
confidence: 99%